Associations between right inferior frontal gyrus morphometry and inhibitory control in individuals with nicotine dependence. (1st March 2023) - Brown, Alexander A.; Upton, Spencer; Craig, Stephen; Froeliger, Brett
Abstract: Background: The hyperdirect pathway - a circuit involved in executing inhibitory control (IC) - is dysregulated among individuals with nicotine dependence. The right inferior frontal gyrus (rIFG), a cortical input to the hyperdirect circuit, has been shown to be functionally and structurally altered among nicotine-dependent people who smoke. The rIFG is composed of 3 cytoarchitecturally distinct subregions: The pars opercularis, pars triangularis, and pars orbitalis. The present study assessed the relationship between rIFG subregion morphometry and inhibitory control among individuals with nicotine dependence. Methods: Behavioral and magnetic resonance brain imaging (MRI) data from 127 nicotine-dependent adults who smoke ( M FTND = 5.4, ± 1.9; M CPD = 18.3, ± 7.0; M years = 25.04, ± 11.97) ( M age = 42.9, ± 11.1) were assessed. Brain morphometry was assessed from T1-weighted MRIs using Freesurfer. IC was assessed with a response-inhibition Go/Go/No-Go (GGNG) task and a smoking relapse analog task (SRT). Results and conclusions: Vertex-wise analyses revealed that GGNG task scores were positively associated with cortical thickness and volume in the right pars triangularis (cluster-wise p = 0.006, 90% CI = 0.003 – 0.009; cluster-wise p = 0.040, 90% CI = 0.032 – 0.048), and the ability to inhibit ad lib smoking during the SRT was positively associated with cortical thickness in the right pars orbitalis (cluster-wise p = 0.011, 90% CI = 0.007 – 0.015). Our results indicate that cortical thickness of distinct rIFG subregions may serve as biomarkers for unique forms of IC deficits. Highlights: Inhibitory control is associated with right inferior frontal gyrus morphometry. Pars orbitalis thickness is associated with inhibition of ad lib smoking. Pars triangularis thickness & volume is associated with motor response inhibition. rIFG subregion morphometry shows heterogeneity based on associations with different forms of inhibitory control.